PERBANDINGAN HASIL INR (International Normalized Ratio) SEBELUM DAN SESUDAH TERAPI HEPARIN WARFARIN PADA PASIEN PENYAKIT JANTUNG KORONER DI RUMAH SAKIT ATMA JAYA JAKARTA UTARA - Setiawan, Heru; Venna, Venna; Debora Turnip, Lowisa (Jurnal Fisioterapi dan Kesehatan Indonesia, 2025)
Coronary Heart Disease (CHD) is a disorder of heart function due to a lack of blood in the heart muscle due to narrowing or blockage of the coronary arteries caused by atherosclerosis. This occurs when the heart muscle's supply of oxygen-rich blood is blocked by plaque in the blood vessels leading to the heart blood or coronary arteries. Warfarin is an anticoagulant that is strongly associated with bleeding in CHD. The laboratory examination that is often used to measure prothrombin time and as anticoagulant therapy to detect bleeding disorders is INR (International Normalized Ratio). This study aims to determine the comparison of INR results before and after heparin warfarin therapy in coronary heart disease patients at Atma Jaya Hospital. The method of this research is cross sectional descriptive analysis using 39 RM data from CHD patients who have met the inclusion and exclusion criteria using the Wilcoxon test. These results showed that the average INR value before therapy was 1.849 per second, the average INR value after therapy was 1.316 per second. The Wilcoxon test results showed a difference between INR values ​​before and after therapy (p=0.000) with significance (α=<0.05) in patients on heparin warfarin therapy at Atma Jaya Hospital. From this research, it is hoped that CHD patients will continue to undergo therapy to prevent hemostasis disorders and to avoid the risk of bleeding which can cause death. Keywords: CHD, warfarin, INR.